Beyond the Stethoscope: Burnout Syndrome Among Interns and Postgraduates in a South Indian Tertiary Care Setting - Vijayakarthikeyan M; Megan Sarah Mathew; Raju Kannan S; Sangeetha S (National Journal of Community Medicine)
Background: Burnout is a troubling clinical syndrome characterized by excessive stress, dissatisfaction and a sense of being overworked. Prevalence of burnout varies from 50% to 76%, depending on the specialty across studies. The objectives of the study are to estimate the prevalence of burnout syndrome among interns and residents, and to identify the factors associated with it.